(untitled) (Sociologisk Forskning, 1998)
The aim of this article is to analyse individual careers towards, during and out of drug use, drawing on the sensitizing concepts of subjective and objective career as analytical tools. Two significant groups can be found, the marginalised and the integrated. The marginalised have experienced insecure relations with their parents. Their experiences of critical incidents have brought about feelings of a lack of continuity in their own narrative. These violations affect the individual’s self conception. Their interpretation of the incidents causes feelings of shame and not belonging. In interaction with others they feel that they lack the cultural capital that is needed, which often increases the feeling of shame. These emotions are also a threat to the individual’s social bonds in more conventional settings. In order to reduce these negative emotions they have to leave settings where those emotions appear. They have to find other settings where new social bonds can be built. The individuals in the second group, the integrated, do not use drugs because their own identity is constantly in question. They have not experienced feelings of shame and there are not any threats to their social bonds to conventional groups. Their drug habit is also often integrated with other more conventional activities. The individuals in this group have also acquired a cultural capital from previous interactional chains, such as the family and education, that is adequate in conventional contexts. They have a competence to display roles in other contexts outside the drug setting.